Obligations innovative as a mechanism for contractual balance the execution of the contract. - Billami, Sarah (Journal of Human Sciences, 2022)
Recent economic, social and technological developments have demonstrated the inadequacy and inability of the classic contract theory based on the principle of the authority of will and binding power of the contract to achieve contract balance and contractual justice in the phase of execution of the contract. This prompted jurisprudence and the judiciary to develop a number of obligations (innovative obligations) at the implementation stage of the contract, in order to address the shortcomings of the principle of binding force of the contract at this stage, many private legislations hastened to establish them by stipulating them specifically in certain contracts., or to consider them applications resulting from the principle of good faith in the execution of the contract.